ANALYSIS OF GRADE XII STUDENTS’ CRITICAL THINKING SKILLS IN SOLVING LINEAR PROGRAMMING PROBLEMS BASED ON MATHEMATICAL ABILITY - Arfandi Nur Wahid; Alfisyahra Alfisyahra; Muh. Rizal (Universitas Sembilanbelas November Kolaka, 2026)
This study aims to describe students' critical thinking skills in solving linear programming problems in grade XII in terms of their mathematical ability level. This study uses a qualitative descriptive approach with three grade XII students selected through purposive sampling technique as subjects, each representing high, medium, and low levels of mathematical ability. The research data were obtained through a linear programming problem-solving test instrument and in-depth interviews which were analyzed through data condensation, data presentation, and conclusion drawing. The results obtained indicate that high-ability students use all critical thinking indicators. They are able to formulate problems, model mathematics, check and solve problems, draw detailed conclusions, write and explain the final answer in detail, and review the answers obtained. Meanwhile, students with medium ability also fulfill all indicators. They are able to formulate problems, model mathematics, check and solve problems, draw conclusions, write and explain the final answer, and review the answers. Meanwhile, low-ability students only master three critical thinking indicators: formulating problems, modeling mathematics, and checking and solving problems. Overall, the difference in students' mathematical ability levels is directly proportional to the depth of achievement of critical thinking indicators in solving linear programming problems.